2018
DOI: 10.1167/iovs.18-25137
|View full text |Cite
|
Sign up to set email alerts
|

The Carnitine Shuttle Pathway is Altered in Patients With Neovascular Age-Related Macular Degeneration

Abstract: PurposeTo identify metabolites and metabolic pathways altered in neovascular age-related macular degeneration (NVAMD).MethodsWe performed metabolomics analysis using high-resolution C18 liquid chromatography-mass spectrometry on plasma samples from 100 NVAMD patients and 192 controls. Data for mass/charge ratio ranging from 85 to 850 were captured, and metabolic features were extracted using xMSanalyzer. Nested feature selection was used to identify metabolites that discriminated between NVAMD patients and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 40 publications
4
63
0
Order By: Relevance
“…Valerylcarnitine is a short-chain fatty acid (C5) associated with carnitine. The alteration of the carnitine shuttle was already identified in metabolomics studies as a key feature of neovascular AMD [19]. Our study shows that, in addition to the long-chain acylcarnitines already reported, short-chain acylcarnitines such as valerylcarnitine can also be involved, as well as the fatty acids carrier itself, carnitine.…”
Section: Discussionsupporting
confidence: 70%
“…Valerylcarnitine is a short-chain fatty acid (C5) associated with carnitine. The alteration of the carnitine shuttle was already identified in metabolomics studies as a key feature of neovascular AMD [19]. Our study shows that, in addition to the long-chain acylcarnitines already reported, short-chain acylcarnitines such as valerylcarnitine can also be involved, as well as the fatty acids carrier itself, carnitine.…”
Section: Discussionsupporting
confidence: 70%
“…Recently, the limitations of the original paper by Osborn et al [126] have been improved on in a study, which investigated the metabolites and associated metabolic pathways of a larger cohort of NVAMD patients [131]. Plasma samples were collected from NVAMD patients, who exhibited extensive CNV, subretinal hemorrhaging or fibrosis, or photocoagulation scarring in one or both eyes.…”
Section: Metabolomics In Amdmentioning
confidence: 99%
“…Plasma aliquots (65 μL) were treated with 130 μL acetonitrile (2:1 volume/volume) containing 3.5 μL of an internal isotopic standard mix and placed on ice for 30 minutes. [ 14 17 ] The internal standard mix consisted of 14 stable isotopic chemicals, [ 14 ] which cover a broad range of chemical properties represented in small molecules: [ 13 C 6 ]-d-glucose, [ 15 N]-indole, [2- 15 N]-l-lysine dihydrochloride, [ 13 C 5 ]-l-glutamic acid, [ 13 C 7 ]-benzoic acid, [3,4- 13 C 2 ]-cholesterol, [ 15 N]-l-tyrosine, [trimethyl- 13 C 3 ]-caffeine, [ 15 N 2 ]-uracil, [3,3- 13 C 2 ]-cystine, [1,2- 13 C 2 ]-palmitic acid, [ 15 N, 13 C 5 ]-l-methionine, [ 15 N]-choline chloride, and 2’-deoxyguanosine- 15 N 2 , 13 C 10 -5’-monophosphate. Samples were analyzed using a Thermo LTQ Velos Orbitrap high-resolution (60,000 mass resolution) mass spectrometer (Thermo Fisher Scientific, San Diego, California) and C18 column chromatography (Higgins Analytical Inc., Targa, 2.1 × 10 cm) in positive ionization mode with a scanning m/z range of 85–2000 over 10 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…All subjects underwent an overnight fast before blood collection and untargeted high-resolution metabolomic profiling using liquid-chromatography mass spectrometry (LC/MS) was performed using standardized techniques after thawing each subject's plasma stored at -80C elsius. [11][12][13][14][15][16][17] Plasma samples were run in a randomized order in batches of 20 and three technical replicates were analyzed for each sample in a sequential manner. Plasma aliquots (65 μL) were treated with 130 μL acetonitrile (2:1 volume/volume) containing 3.5 μL of an internal isotopic standard mix and placed on ice for 30 minutes.…”
Section: High-resolution Metabolomic Profilingmentioning
confidence: 99%
See 1 more Smart Citation